The role of osteomodulin on osteo/odontogenic differentiation in human dental pulp stem cells - Wenzhen Lin; Li Gao; Wenxin Jiang; Chenguang Niu; Keyong Yuan; Xuchen Hu; Rui Ma; Zhengwei Huang (BMC, 2019)
Abstract Background Extracellular matrix secretion and odontoblastic differentiation in human dental pulp stem cells (hDPSCs) are the cellular bases for reparative dentinogenesis. Osteomodulin (OMD) is a member of the small leucine-rich proteoglycan family distributed in the extracellular matrix but little is known about its role in osteo/odontogenic differentiation. The objective of this study was to investigate the role of OMD during osteo/odontoblastic differentiation of hDPSCs. Methods hDPSCs were selected using immune-magnetic beads and their capability of multi-differentiation was identified. OMD knockdown was achieved using short hairpin RNA (shRNA) lentivirus and was confirmed by western blot. Gene expression was measured by real-time qPCR and osteo/odontoblastic differentiation of hDPSCs was determined by alizarin red S staining. Results Compared with uninduced cells, the transcription of OMD was up-regulated by 35-fold at the late stage of osteo/odontogenic differentiation. shRNA-mediated gene silencing of OMD decreased the expression of odontoblastic genes, such as alkaline phosphatase (ALP), dentin matrix acidic phosphoprotein 1 (DMP1) and dentin sialophosphoprotein (DSPP). Besides, knockdown of OMD attenuated the mineralized nodules formation induced by osteo/odontogenic medium. Conclusions These results implied that OMD may play a pivotal role in modulating the osteo/odontoblastic differentiation of hDPSCs.